Meta-analysis of sutureless technology versus standard aortic valve replacement and transcatheter aortic valve replacement. (12th September 2017) - Qureshi, Saqib H; Boulemden, Anas; Szafranek, Adam; Vohra, Hunaid
Abstract: OBJECTIVES: Aortic valve replacement (AVR) using sutureless technology is a feasible alternative in surgical patients. Comparative evidence against established strategies such as conventional AVR and transcatheter AVR is lacking, limiting the assessment of safety and efficacy. METHODS: Medline search for available evidence was undertaken. The outcomes analysed were 30-day mortality, risk for stroke, myocardial infarction, renal failure, paravalvular leak and need for permanent pacemaker. Odds ratios were pooled using fixed- and random-effect models. A trial sequential analysis was undertaken to assess the statistical reliability of cumulative evidence. RESULTS: Twelve studies of moderate methodological quality were included. Sutureless AVR was associated with at least 30% reduction in 30-day mortality versus transcatheter AVR [odds ratio (95% confidence interval) 0.40 (0.25, 0.62); P  < 0.001] primarily in the low- and intermediate-risk population and a similar reduction in the risk for paravalvular leak [0.13 (0.09, 0.17); P  < 0.001]. There was no reduction in the risk for 30-day mortality versus conventional AVR [1.03 (0.56, 1.88); P  = 0.93]. There was evidence in favour of conventional AVR with at least 50% risk reduction in pacemaker implantation against sutureless technology. There was absence of either benefit or harm vis-à-vis risk for renal injury or stroke due to lack of required information size. CONCLUSIONS: Current evidence suggests risk reduction in 30-day mortality with sutureless AVR versus transcatheter AVR but is inconclusive versus standard AVR in matched patients. Robust randomized evidence is lacking to lend support to any potential recommendation.